The IsomiR Window: the interface that bridges the complexity of miRNAs and their functional impact - Ferreira, Beatriz Viamonte de Sousa (2017)
Tese de mestrado, Bioinformática e Biologia Computacional (Bioinformática), Universidade de Lisboa, Faculdade de Ciências, 2017